2018
DOI: 10.3171/2017.2.jns163191
|View full text |Cite
|
Sign up to set email alerts
|

Folate receptor overexpression can be visualized in real time during pituitary adenoma endoscopic transsphenoidal surgery with near-infrared imaging

Abstract: OBJECTIVE Pituitary adenomas account for approximately 10% of intracranial tumors and have an estimated prevalence of 15%-20% in the general US population. Resection is the primary treatment for pituitary adenomas, and the transsphenoidal approach remains the most common. The greatest challenge with pituitary adenomas is that 20% of patients develop tumor recurrence. Current approaches to reduce recurrence, such as intraoperative MRI, are costly, associated with high false-positive rates, and not recommended. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…Preliminary work with OTL38, a folate analog conjugated to an analog of ICG, for pituitary adenomas suggests that it may be possible to delineate tumor margins with a high degree of sensitivity and specificity, specifically in adenomas with high folate receptor α expression . OTL38 functions in the NIR spectrum because of its conjugation with an ICG analog, and has the additional advantage of being a tumor‐specific dye, like 5‐ALA.…”
Section: Intraoperative Considerationsmentioning
confidence: 99%
“…Preliminary work with OTL38, a folate analog conjugated to an analog of ICG, for pituitary adenomas suggests that it may be possible to delineate tumor margins with a high degree of sensitivity and specificity, specifically in adenomas with high folate receptor α expression . OTL38 functions in the NIR spectrum because of its conjugation with an ICG analog, and has the additional advantage of being a tumor‐specific dye, like 5‐ALA.…”
Section: Intraoperative Considerationsmentioning
confidence: 99%
“…Use of fluorescence did not interfere with the surgeon's ability to perform the procedure. This “first-in-human” study demonstrates potential for use of small molecules to target ovarian cancer, guide radical cytoreductive surgery, and improve methods for intraoperative staging [ 62 69 ].…”
Section: Targeted Optical Imaging Agentsmentioning
confidence: 99%
“…In conclusion, the new 2017 classification is practical and reasonable from both a molecular and clinical pathology perspective, as this classification is based on IHC studies of transcription factors, which are intuitively understandable and are technically and diagnostically helpful (26). The present study is not the first clinicopathological analysis of pituitary adenomas based on the new classification (26,(47)(48)(49)(50), however previous studies have also showed that the new WHO 2017 classification categorizes less null cell adenomas compared with previous classifications (26,47). In the present study, patients with pituitary tumour diagnosed after 2017 were systematically classified according to the 2017 classification criteria and provides a theoretical basis for the accurate diagnosis of PAs.…”
Section: Group ------------------------------------------------------mentioning
confidence: 80%